2020
DOI: 10.1088/1742-6596/1481/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Cd (II) ion from aqueous solution using immobilized Lengkeng (euphoria longan lour) shell

Abstract: In this paper, lengkeng shell was immobilization with sodium silica yo remove Cd (II) ion from aqueous soution by biosorption was investigative in a batch system immobilization of lengkeng shell can improve the ability of biosorbent in the process of absorption. The influence of solution pH and particle size. Were evaluated the result showed that the absorbent was good for the removal of Cd (II) ion with biosorption capacity of 22.587 mg/g at pH 5 and 250 μm particle size. Immobilization lengkeng shell showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 0 publications
1
10
0
8
Order By: Relevance
“…The adsorption of metal ions depends on the type of surface of the adsorbent and on the form of ions found in the metal in aqueous solution, the more adsorbent, the greater the surface area, thus increasing the active site of the adsorbent surface which results in the amount of Pb metal binding to the active site increasing. [9]. The influence of the adsorbent weight varies from 0.2 to 0.5 grams and the effect can be seen in Figure 1.…”
Section: Analysis Of Characterization Resultsmentioning
confidence: 96%
“…The adsorption of metal ions depends on the type of surface of the adsorbent and on the form of ions found in the metal in aqueous solution, the more adsorbent, the greater the surface area, thus increasing the active site of the adsorbent surface which results in the amount of Pb metal binding to the active site increasing. [9]. The influence of the adsorbent weight varies from 0.2 to 0.5 grams and the effect can be seen in Figure 1.…”
Section: Analysis Of Characterization Resultsmentioning
confidence: 96%
“…In addition, the effect of contact time is closely associated with the general rule of biosorption process in which a longer contact time will enhance the adsorptive capacity. 36 The adsorption in the first 30 min of DBT desulfurization was quite low, but it increased over time until reaching a maximum at the 60-min time interval. Beyond this, ADS reached equilibrium and started decreasing.…”
Section: ■ Ads Optimizationmentioning
confidence: 96%
“…in 2015, in the previous study, the functional group that was identified was in the form of OH streching which could be read at wavenumbers 3304.6 and 3289.63 cm-1 which came from hydroxyl groups in alcohols and carboxylic acids at wavenumbers ranging from 3600 to 3200 cm-1 in the FTIR spectrum. Then the identification of the C-H Stretching functional group at the wavenumber 2924.74 cm-1 and group of C=O streching from the ester compound group at the wavenumber 1635.02 cm-1 [15] [16]. Litchi peel Adsorbent is used to overcome the contamination of metal ions Cu(II) and Pb (II) in liquid waste.…”
Section: Characterization Of Samplementioning
confidence: 99%
“…Some adsorbents that have been used previously to overcome methylene blue and rhodamine B dyes contamination in solution are as follows from longan seeds, langsat peel, reeds, peanut shells, coffee grounds, banana peel, pineapple leaves, tamarind seeds, snail shells, eggshells, and small crab shells [3] [12]. In previous research, Kurniawati [13][14] used longan fruit peel waste as a adsorbent to absorb Cu 2+ and Cd 2+ metals in solution. This is also the background of this study to find out other advantages of longan peel in the absorption of organic substances in solution.…”
Section: Introductionmentioning
confidence: 99%